DIPLOMASI EKONOMI INDONESIA TERHADAP AFRIKA SELATAN DALAM MENINGKATKAN EKSPOR PRODUK MINYAK KELAPA SAWIT PERIODE 2015 - 2018 - Januar Faisal Ramdhan, (2020)
South Africa is a potential market for Indonesian products. By seeing this, the oil palm market opportunity in South Africa is one of the things that can be utilized by Indonesia in dominating the South African market. In an effort to control the market, it is necessary to have economic diplomacy efforts undertaken by Indonesia towards South Africa. The use of economic diplomacy not only aims to control the palm oil market in South Africa but also becomes a tool in dealing with various obstacles that arise in the trade cooperation between the two countries.